Pleiotropic effects of the wheat domestication gene Q on yield and grain morphology - Xie, Quan; Li, Na; Yang, Yang; Lv, Yulong; Yao, Hongni; Wei, Rong; Sparkes, Debbie L.; Ma, Zhengqiang (Springer, 2018)
Transformation from q to Q during wheat domestication functioned outside the boundary of threshability to increase yield, grains m−2, grain weight and roundness, but to reduce grains per spike/spikelet. Mutation of the Q gene, well-known affecting wheat spike structure, represents a key domestication step in the formation of today’s free-threshing, economically important wheats. In a previous study, multiple yield components and spike characteristics were associated with the Q gene interval in the bread wheat ‘Forno’ × European spelt ‘Oberkulmer’ recombinant inbred line population. Here, we reported that this interval was also associated with grain yield, grains m−2, grain morphology, and spike dry weight at anthesis. To clarify the roles of Q in agronomic trait performance, a functional marker for the Q gene was developed. Analysis of allelic effects showed that the bread wheat Q allele conferred free-threshing habit, soft glumes, and short and compact spikes compared with q. In addition, the Q allele contributed to higher grain yield, more grains m−2, and higher thousand grain weight, whereas q contributed to more grains per spike/spikelet likely resulting from increased preanthesis spike growth. For grain morphology, the Q allele was associated with reduced ratio of grain length to height, indicating a rounder grain. These results are supported by analysis of four Q mutant lines in the Chinese Spring background. Therefore, the transition from q to Q during wheat domestication had profound effects on grain yield and grain shape evolution as well, being a consequence of pleiotropy.